Long-Circulating Lipid Nanospheres Loaded with Flurbiprofen Axetil for Targeted Rheumatoid Arthritis Treatment - Chen Z; Liu Z; Wang S; Cheng C; Sun X; Liu Z; Wei J; Jiang J; Lan H; Zhou M; Jing P; Lin Y; et al. (International Journal of Nanomedicine, 2023)
Zhenyu Chen,1,2,* Zhongbing Liu,1,* Shuzao Wang,1,* Cai Cheng,1,* Xiaoduan Sun,1 Zerong Liu,3 Jun Wei,1 Jun Jiang,4,5 Huaqi Lan,1 Meiling Zhou,6 Pei Jing,6 Yan Lin,1 Xiangyu Zhou,7 Zhirong Zhong1,3,8 1Key Laboratory of Medical Electrophysiology, Ministry of Education, School of Pharmacy, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 2The Second People’s Hospital of China Three Gorges University, Yichang, 443000, People’s Republic of China; 3Central Nervous System Drug Key Laboratory of Sichuan Province, Luzhou, Sichuan, 646000, People’s Republic of China; 4Department of General Surgery (Thyroid Surgery), the Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 5Metabolic Vascular Diseases Key Laboratory of Sichuan Province, Luzhou, Sichuan, 646000, People’s Republic of China; 6Department of Pharmacy, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 7Department of Thyroid and Vascular Surgery, the Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 8Key Laboratory of Luzhou City for Aging Medicine, Department of Pharmacology, School of Pharmacy, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiangyu Zhou; Zhirong Zhong, Email xiangyuzhou971@vip.126.com; zhongzhirong@126.comBackground: Flurbiprofen axetil (FA) is a non-steroidal anti-inflammatory drug with good analgesic and anti-inflammatory effects. However, it suffers from poor solubility, short circulation time, and off-target binding profile, which significantly limit its clinical application. Here, we loaded FA into stealth lipid microspheres modified with the arginine-glycine-aspartic acid (RGD) peptide (cRGD-FA-SLM), and examined the therapeutic potential of the resulting platform for the treatment of rheumatoid arthritis (RA).Methods: cRGD-FA-SLM was prepared by high pressure homogenization, and its toxicity and uptake by macrophages were examined using cultures of RAW264.7 cells. Hemolysis and hepatotoxicity tests were performed to assess the safety of the developed platform, while its pharmacokinetics, biodistribution, and therapeutic efficacy were investigated in a collagen-induced arthritis rat model.Results: cRGD-FA-SLM showed homogeneous spherical morphology and efficient encapsulation of FA. The developed platform was non-toxic to normal macrophages and was selectively internalized by lipopolysaccharide-activated macrophages in vitro, while it distributed mainly to arthritic joints and significantly prolonged FA in circulation in vivo. cRGD-FA-SLM also significantly reduced the expression of prostaglandin E2 and alleviated joint edema and bone erosion, showing prolonged analgesic effects in arthritic rats.Conclusion: cRGD-FA-SLM shows good inflammation-targeting ability and prolongs drug circulation in vivo, suggesting promise as an anti-inflammatory and analgesic agent for targeted RA treatment.Graphical Abstract: Keywords: flurbiprofen axetil, lipid nanospheres, cRGD, long circulation, rheumatoid arthritis